Psychological Factors Of Intragroup Process Efficiency Within Modern Organizations - Varava, Liudmila; Dekaliuk, Yelyzaveta (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2022)
The article is devoted to consideration of the problematic issue of improving productivity and increasing the efficiency of management, which is faced by the managers of Ukrainian enterprises and organizations providing social services in the competitive market of goods supply in conditions of full-scale war. Since the organization’s high performance indicators may provide an advantage over competitors and boost financial success, each organization, in turn, strives to become a leader and even a monopolist in a competitive market by its own means. Depending on the productivity of such actions, the organization may gain a significant competitive advantage, which is an integral component of business economic opportunities that can be employed to achieve strategic goals and objectives. Given the current economic behavior of business entities, the need to isolate the psychological factors of corporate culture directly affecting the organizational management efficiency is undeniable, since highly professional psychologists and business consultants in this field may contribute to solving problems of organizational interaction. The article analyzes the theoretical background of the corporate culture phenomenon, value orientations and organization in psychological science. The authors’ interpretations of scientific terms from the standpoint of economic, managerial, sociological and psychological approaches are considered. It is noted that corporate culture is driving force of dynamics in organizational changes and collective behavior, which determines the core of activity of the company’s functional divisions. Corporate values are a fundamental psychological factor, being in dyadic interaction with each employee’s personal values. Therefore, the employees’ system of career value orientations should be consistent with the company’s system of professional values, for in synergy these are capable of helping the organization improve its efficiency and achieve the desired goal. A comparative analysis of organizational cultures, career and personal value orientations between the representatives of the Ukrainian metallurgical company "Metinvest" and the American telecommunications company "Koscom Cable Inc" was performed. It has been established that internal integration, mutual exchange of knowledge and management experience, and also improvement of the enterprises’ organizational structure should increase the performance of Ukrainian businesses in wartime.